2010
DOI: 10.1289/ehp.0901608
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Arsenic Impairs Glucose-Stimulated Insulin Secretion in Pancreatic Beta Cells: Involvement of Cellular Adaptive Response to Oxidative Stress

Abstract: BackgroundChronic exposure of humans to inorganic arsenic, a potent environmental oxidative stressor, is associated with incidence of type 2 diabetes (T2D). A key driver in the pathogenesis of T2D is impairment of pancreatic β-cell function, with the hallmark of β-cell function being glucose-stimulated insulin secretion (GSIS). Reactive oxygen species (ROS) derived from glucose metabolism serve as one of the metabolic signals for GSIS. Nuclear factor-erythroid 2–related factor 2 (Nrf2) is a central transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(104 citation statements)
references
References 38 publications
2
100
0
2
Order By: Relevance
“…Consistently with previous research, this result was considered to be related to the dosage of MnCl 2 . Fu et al (2010) reported that the low levels of arsenic significantly enhanced the Nrf2 activity and induced its downstream proteins. It also suggested that the expression of Nrf2 and the downstream protein could be reduced with increasing iron concentration (Zhao et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently with previous research, this result was considered to be related to the dosage of MnCl 2 . Fu et al (2010) reported that the low levels of arsenic significantly enhanced the Nrf2 activity and induced its downstream proteins. It also suggested that the expression of Nrf2 and the downstream protein could be reduced with increasing iron concentration (Zhao et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The latter was deduced from altered expression of the following genes: (1) Pdx1 (previously known as Iuf1) [93][94][95], a transcription factor that is essential for pancreas development, insulin production and glucose homeostasis [96]; and (2) the insulin gene [97]. Other studies reported effects on glucose uptake, induction of ROS production, interference with the activity of key antioxidant enzymes [98], apoptosis, necrosis and inflammation reactions [39,93] (Fig. 2).…”
Section: Metalsmentioning
confidence: 99%
“…ROS clearly possess the capacity to behave in a random and can directly or indirectly activate cellular stress-sensitive signaling pathways [46]. It is well known that ROS generation is believed to be essential in triggering signaling response of insulin [47].…”
Section: Discussionmentioning
confidence: 99%